ENHANCING CRITICAL THINKING ON CLIMATE CHANGE: TPACK IMPLEMENTATION IN PBL WITH DIGITAL POSTERS - Shelly Efwinda; Irma Puspita; Puardmi Damayanti; Abdul Hakim; Muliati Syam (EDUSAINS, 2023)
Critical thinking skills are vital in the 21st Century to identify solutions to real-world problems like climate change. This research aims to test the effect of integrating the PBL (Problem-based Learning) Model with Digital Posters within the TPACK (Technological, Pedagogical, and Content Knowledge) framework on the critical thinking skills of junior high school students in Samarinda on climate change. The research approach used is quantitative with a quasi-experimental method involving two classes, an experimental and a control class. The treatment given to the experimental class was the PBL model with the help of digital posters, and the control class used the traditional lecture method. Data on students' critical thinking skills was collected using a test technique in the form of 10 essay questions. Data analysis techniques used quantitative descriptive and T-tests. The research results showed significant differences in the critical thinking skills of the experimental and control classes after each class was treated. Based on these findings, it recommends the need for similar adoption by teachers in teaching complex topics such as climate change. These results also show the importance of integrating technology in learning to support the development of student's critical thinking skills, especially in understanding complex topics.